Iṭālīno tāraṇahāra Gerībāldī - Vahorā, Rasūlabhāī Na. (Rasūlabhāī Nabījī), 1902-1958 (SAMP early 20th-century Indian books project, 1939)
Biography of Giuseppe Garibaldi, 1807-1882, Italian statesman.